Excessive Accumulation of Ca2 + in Mitochondria of Y522S-RYR1 Knock-in Mice: A Link Between Leak From the Sarcoplasmic Reticulum and Altered Redox State - Canato, Marta; Capitanio, Paola; Cancellara, Lina; Leanza, Luigi; Raffaello, Anna; Reane, Denis Vecellio; Marcucci, Lorenzo; Michelucci, Antonio; Protasi, Feliciano; Reggiani, Carlo (Frontiers in Physiology, 2019)
ABSTRACT Mice (Y522S or YS), carrying a mutation of the sarcoplasmic reticulum (SR) Ca2+ release channel of skeletal muscle fibers (Ryanodine Receptor type-1, RyR1) which causes Ca2+ leak, are a widely accepted and intensively studied model for human malignant hyperthermia (MH) susceptibility. Since the involvement of reactive oxygen species (ROS) and of mitochondria in MH crisis has been previously debated, here we sought to determine Ca2+ uptake in mitochondria and its possible link with ROS production in single fibers isolated from flexor digitorum brevis (FDB) of YS mice. We found that Ca2+ concentration in the mitochondrial matrix, as detected with the ratiometric FRET based 4mtD3cpv probe, was higher in YS than in wild type (WT) fibers at rest and after Ca2+ release from SR during repetitive electrical stimulation or caffeine administration. Also mitochondrial ROS production associated with contractile activity (detected with Mitosox probe) was much higher in YS fibers than in WT. Importantly, the inhibition of mitochondrial Ca2+ uptake achieved by silencing MCU reduced ROS accumulation in the matrix and Ca2+ release from SR. Finally, inhibition of mitochondrial ROS accumulation using Mitotempo reduced SR Ca2+ release in YS fibers exposed to caffeine.The present results support the view that mitochondria take up larger amounts of Ca2+ in YS than in WT fibers and that mitochondrial ROS production substantially contributes to the increased caffeine-sensitivity and to the enhanced Ca2+ release from SR in YS fibers.